Screening of Pathogenic and Non-Pathogenic Bacteria Isolated from Maggot Digestive System - Azhari, Azhari; Sari, Wahyu Eka; Ferasyi, Teuku Reza; Ismail, Ismail; Novita, Andi; Darniati, Darniati; Riady, Ginta; Fadlah, Iga; Rahmadhini, Vivi (The International Journal of Tropical Veterinary and Biomedical Research, 2024)
Maggots are one of the fly larvae with a high protein content of up to 30-45%, so maggots can be used as an alternative animal feed ingredient. As one of the sources of animal feed raw materials, insects-based feed must also be safe from contaminants of microorganisms, including pathogenic bacteria. Therefore, this study aims to isolate and determine the screening of pathogenic and non-pathogenic bacteria from maggots' digestive systems. Maggots are cultivated on media based on animal faecal and organic waste for 2 months. Then, the bacteria are isolated and purified using nutrient agar media, and hemolysis tests are carried out on blood agar media and Gram staining. Eighty-seven bacterial colonies with various morphological characteristics were successfully isolated from the maggot digestive system. Most isolated bacteria are classified as Gram-negative bacteria with a bacilli form. Based on the results of the hemolysis test, as many as 16% of bacterial isolates are indicated by pathogenic bacteria because of their ability to hemolyze blood. However, only about 2% showed b-hemolysis. Thus, it can be concluded that the screening results of non-pathogenic bacteria are still more numerous compared to pathogenic bacteria present in the maggot digestive system.